1991
DOI: 10.1128/jb.173.14.4353-4362.1991
|View full text |Cite
|
Sign up to set email alerts
|

Nucleotide sequence of the Spiroplasma citri fibril protein gene

Abstract: Electron microscopic observation of spiroplasmas lysed by detergent (sodium deoxycholate) revealed the release of bundles of fibrils from the cells. Individual fibrils are 4 nm in diameter and possess a 9-nm periodicity along their length. These fibrils are thought to function as cytoskeletal structures involved in the shape and motility of spiroplasmas. Polyacrylamide gel electrophoresis of density gradient-purified fibrils showed a protein of approximately 55 kDa. Oligonucleotide probes were constructed from… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

4
52
0

Year Published

1992
1992
2020
2020

Publication Types

Select...
6
3

Relationship

3
6

Authors

Journals

citations
Cited by 65 publications
(56 citation statements)
references
References 30 publications
4
52
0
Order By: Relevance
“…1), which harbors the tetM gene (25) from the transposon Tn916 inserted into the pBS plasmid (Stratagene, La Jolla, Calif.). In pSRT2, the tetM gene is under the control of the S. citri spiralin gene promoter (40). The 1.9-kbp oriC region of M. pulmonis, containing the dnaA gene with its upstream and downstream intergenic regions ( Fig.…”
Section: Methodsmentioning
confidence: 99%
“…1), which harbors the tetM gene (25) from the transposon Tn916 inserted into the pBS plasmid (Stratagene, La Jolla, Calif.). In pSRT2, the tetM gene is under the control of the S. citri spiralin gene promoter (40). The 1.9-kbp oriC region of M. pulmonis, containing the dnaA gene with its upstream and downstream intergenic regions ( Fig.…”
Section: Methodsmentioning
confidence: 99%
“…Large-scale and small-scale preparations of plasmids and M13 DNA amplified in E. coli were carried out according to standard procedures (37). Isolation of spiroplasmal genomic DNA has been described elsewhere (51).…”
Section: Methodsmentioning
confidence: 99%
“…Sequence determination of several spiroplasmal genes has shown that both UGG and UGA are used as tryptophan codons (5,7,28,38). In the present study, we analyzed the tRNATrP situation in S. citri.…”
mentioning
confidence: 99%